INVESTIGATING THE INFLUENCE OF CONTINUOUS INTEGRATION ON SOFTWARE QUALITY AND DEVELOPER PRODUCTIVITY - Faryal Gul; Muhammad Ijaz Khan (Spectrum of Engineering Sciences, 2025)
Continuous Integration (CI) has emerged as a pivotal practice in modern software development, impacting both software quality and developer productivity. This study conducts a systematic literature review (SLR) to investigate the reported claims regarding the effects of CI on software development processes. The synthesis of findings from diverse sources provides a nuanced understanding of CI practices, tools, and their influence on software quality parameters and developer productivity. The SLR focuses on key aspects, including code stability, bug detection, release confidence, collaboration, issue resolution, and documentation. The study uncovers insights into the multifaceted role of CI in shaping software quality and explores its implications for developers working in various environments. Additionally, the research identifies challenges, contributions, and limitations within the existing literature. While the study contributes valuable insights, it recognizes certain limitations, such as the dynamic nature of CI practices and the heterogeneity of development environments. The findings highlight the need for continuous monitoring of emerging trends, empirical validation of reported claims, and exploration of the integration of CI with emerging technologies. This study provides a comprehensive overview of the influence of CI on software development, contributing to the ongoing discourse on effective software engineering practices. The identified challenges and avenues for future research guide the way for further exploration, refinement, and adaptation of CI practices in the ever-evolving landscape of modern software development.